2012
DOI: 10.1124/jpet.112.198226
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Phosphatase as a Treatment of Sepsis-Associated Acute Kidney Injury

Abstract: Currently there are no pharmacological therapies licensed to treat sepsis-associated acute kidney injury (AKI). Considering the high incidence and mortality of sepsis-associated AKI, there is an urgent medical need to develop effective pharmacological interventions. Two phase II clinical trials recently demonstrated beneficial effects of the enzyme alkaline phosphatase (AP). In critically ill patients with sepsis-associated AKI, treatment with AP reduced the urinary excretion of tubular injury biomarkers and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 59 publications
2
40
0
Order By: Relevance
“…41,42 The therapeutic efficacy of AP has been attributed to AP-mediated dephosphorylation/detoxification of lipopolysaccharide and dephosphorylation of ATP, a proinflammatory energy molecule released by inflamed renal tissue. 40 In the present study, we have shown that the addition of AP abolished thrombin generation in PRP, suggesting that AP may also exert beneficial effects by impairing platelet polyP-dependent activation of coagulation.…”
Section: -4mentioning
confidence: 71%
See 1 more Smart Citation
“…41,42 The therapeutic efficacy of AP has been attributed to AP-mediated dephosphorylation/detoxification of lipopolysaccharide and dephosphorylation of ATP, a proinflammatory energy molecule released by inflamed renal tissue. 40 In the present study, we have shown that the addition of AP abolished thrombin generation in PRP, suggesting that AP may also exert beneficial effects by impairing platelet polyP-dependent activation of coagulation.…”
Section: -4mentioning
confidence: 71%
“…Recent studies have suggested a therapeutic use for AP in the treatment of sepsis-associated organ dysfunction. 40 Two phase II studies demonstrated that parenteral administration of the dephosphorylating enzyme AP to intensive care unit patients with sepsis and associated acute kidney injury improved kidney function and reduced markers of inflammation and kidney injury. 41,42 The therapeutic efficacy of AP has been attributed to AP-mediated dephosphorylation/detoxification of lipopolysaccharide and dephosphorylation of ATP, a proinflammatory energy molecule released by inflamed renal tissue.…”
Section: -4mentioning
confidence: 99%
“…Alkaline phosphatase obtunds the Sepsis-Induced Acute Kidney Injury inflammatory response by detoxifying endotoxin, and by attenuating RNS production. 59 Intravenous injection of alkaline phosphatase in patients with early septic AKI significantly improved creatinine clearance with a trend toward a reduced need for RRT. 60 No large RCT has yet explored its efficacy in septic humans.…”
Section: Future Therapiesmentioning
confidence: 98%
“…In addition, there are four potential mechanisms by which the plasma membrane can play an important role in AKI that could be fruitful subjects for further research: by alterations in (1) membrane composition, (2) membrane-associated proteins, and (3) membrane-associated enzymatic activity, and by (4) signaling by membrane-associated components. Examples for each of these potential roles for the plasma membrane in AKI include the following: (1) the composition of cholesterol-rich microdomains is altered after AKI, and lipid microdomains are important both for preventing cell injury and developing subsequent cytoresistance to further insult 1,2 ; (2) there is increased expression of FAS ligand, 3 altered caveolin-1 expression, 4,5 and decreased Na transporters after AKI 6 ; (3) decreased membrane-associated alkaline phosphatase 7 and altered expression of the zinc-dependent metalloproteinase meprin A are associated with AKI 8 ; and (4) a potential role has been suggested for microvesicles/exosomes in protection and recovery from AKI. 9,10 Recent studies have highlighted the importance of regulated necrosis or necroptosis, a receptor-interacting protein kinase-dependent necrotic cell death in AKI.…”
Section: Cell Membranementioning
confidence: 99%